Concurrent changes in physical activity and physical functioning during retirement transition-a multi-trajectory analysis. - Roosa Lintuaho; Mikhail Saltychev; Jaana Pentti; Jussi Vahtera; Sari Stenholm (PLoS ONE, 2023)
Background Physical activity and physical functioning have been reported to change over retirement transition, but the results have been inconsistent, and the two constructs have not been studied concurrently. The objective of this study was to examine concurrent changes in physical activity and physical functioning during transition to retirement among public sector employees, and to examine if occupation, sex, marital status, body mass index (BMI), alcohol consumption and smoking status are associated with observed different multi-trajectory paths. Methods 3,550 participants of the Finnish Retirement and Aging study responded to an annual survey on physical activity and physical functioning (SF-36) before and after retirement. Group-based multi-trajectory analysis was used to identify clusters with dissimilar concurrent changes in physical activity and physical functioning. Multinomial regression analysis was used to describe the associations between covariates and the probability of being classified to a certain cluster. Results Participants were 63.4 (SD 1.4) years old, 83% women, 65% professional workers. Four trajectories of concurrent changes in physical activity and physical functioning were identified, one with decreasing physical functioning and low activity, one with increasing high activity and stable high functioning and two with fluctuating moderate physical activity and stable high functioning. Single, women, obese participants and risk-users of alcohol were more likely to be classified into group with low physical activity and declining physical functioning. Conclusions Low physical activity below the level usually recommended was associated with lower physical functioning during retirement transition. These findings could be useful when planning interventions for retirees to maintain their physical functioning level.